Analisis Fi’il Mudhari dalam Al Qur’an Surat Yasin - Siti Khodijah; Angger Putri Mahardini; Masyfiatul Asriyah (Program Studi Pendidikan Bahasa Arab, 2023)
The background of this research is the importance of understanding the science of nahwu which is very influential on the meaning of sentences and the number of inaccurate understandings of Fi'il Mudhori. This thesis discusses about Fi'il Mudhori in the Al-Qur'an Surah Yasin. The formulation of the problem in this research is how the form of the use of Fi'il Mudhori in Surat Yasin. In addition, this study aims to identify and describe the analysis of Fi'il Mudhori through the nahwu science approach and to find out the number of Fi'il Mudhori in Yasin's letter. This research is a library research, namely research that takes research materials from several references or books that are in accordance with the research theme by taking from the Qur'an letter Yasin using descriptive analysis. The data collection by means of observation of the primary and secondary data sources qualitatively.The structure of Fi'il Mudhori in Surah Yasin is very diverse, which includes Fi'il Shohih, Fi'il Mu'tal which is mujarrad and Mazid both Tsulasi, Rubai, Khumasi, and Sudasi. The results of the research from Yasin's letter contained 84 Fi'il Mudhori with descriptions such as: Fi'il Salim amounted to 40 Fi'il Mudhori, Fi'il Mahmuz amounted to 26 Fi'il Mudhori, Fi'il Mudha'af amounted to 1 Fi'il Mudhari, Fi'il Mudhari 'il Misal is 1 Fi'il Mudhori, Fi'il Ajwaf is 2 Fi'il Mudhori, Fi'il Naqish is 14 Fi'il Mudhori, In conclusion there are 84 Fi'il Mudhori' and 51 verses in the Qur'an Surah Yasin Through this research is expected to provide benefits and can be used as research literature Literature Review.